Krisis Kemanusiaan Etnis Rohingnya: Partisipasi Warga Dunia dan Peran Pemerintah Indonesia - Kusnadi, Arianti; Ananta, Chansa; Nurnajah, Ighna Karimah; Akbar, Muhamad Fadillah (Gunung Djati Conference Series, 2025)
This research attempts to resolve the Rohingya conflict in three stages. The first since the Myanmar government discriminated against its people. Second after the Rohingya people tried to seek protection by fleeing to other countries. Third, when the Rohingya entered Indonesia and saw how the Indonesian government responded in efforts to mediate with Myanmar. The aim is to specifically look at the Indonesian government’s strategy by using cosmopolitan theory in viewing Indonesia’s existence in the international arena. This research uses a qualitative method with a literature study research design that utilizes both physical and non-physical information. This research uses cosmopolitan theory in looking at the phenomena that occur. The ethnic conflict in Myanmar is a historical conflict, which has never been resolved and has entered the humanitarian crisis stage. The humanitarian crisis experienced by the Rohingya ethnic group in Myanmar, which was triggered by systematic and prolonged discrimination, has led to a mass exodus to neighboring countries with dire conditions. Because of its application to other countries, all countries or international organizations are trying to find a way out of this problem.